'Everything went according to the rules'. Female citizen sponsors' legal consciousness, intimate citizenship and family migration law. Issue 1 (2nd January 2021) - de Hart, Betty; Besselsen, Elles
ABSTRACT: Academic literature has studied the legal consciousness of common citizens: the way ordinary people think and talk about law in their everyday lives. Building on this literature, we explore how Dutch female citizens with a migrant partner experience the impact of migration law on their everyday lives. We questioned how legal consciousness is linked to intimate citizenship, thus demonstrating how 'private' matters such as intimate relationships, marriage, and family have a profound impact on citizenship. Based on two sets of interviews, conducted in 2000 and 2016, we were able to determine how these women, despite being citizens formally, experienced the profound impact of increasingly restrictive family reunification policies. Contrary to our expectations, female sponsors continued to express considerable support for restrictive migration law. In performing intimate citizenship, they claimed an exception from the strict application of the rules for their particular family situation, rather than radical change.